Analisis Sistem Antrian Kartu Tanda Penduduk (KTP) di Kantor Dinas Kependudukan dan Catatan Sipil Kabupaten Barru - Wahidah Alwi; Adiatma; Andi Nurfadhilah (Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines the queuing system for e-KTP recording services at the Population and Civil Registration Office of Barru Regency. Using a Multi-Channel Single-Phase queue model, the objective is to optimize the queuing process and evaluate system performance. The Multi-Channel Single-Phase model is applied because the service involves a single type of process with multiple service facilities. The findings show that, over a five-day observation period, the system achieved a performance efficiency level with a steady-state measure of ρ < 1, indicating that steady-state conditions were satisfied. Thus, the results suggest that the e-KTP recording services at the Population and Civil Registration Office of Barru Regency operate optimally.